Epileptic phenotypes in autoimmune encephalitis: from acute symptomatic seizures to autoimmune-associated epilepsy. Issue 11 (25th July 2022) - Matricardi, Sara; Casciato, Sara; Bozzetti, Silvia; Mariotto, Sara; Stabile, Andrea; Freri, Elena; Deleo, Francesco; Sartori, Stefano; Nosadini, Margherita; Pappalardo, Irene; Meletti, Stefano; Giovannini, Giada; et al.
Abstract : Objective: To describe the clinical and paraclinical findings, treatment options and long-term outcomes in autoimmune encephalitis (AE), with a close look to epilepsy. Methods: In this retrospective observational cohort study, we enrolled patients with new-onset seizures in the context of AE. We compared clinical and paraclinical findings in patients with and without evidence of antibodies. Results: Overall, 263 patients (138 females; median age 55 years, range 4–86) were followed up for a median time of 30 months (range 12–120). Antineuronal antibodies were detected in 63.50%. Antibody-positive patients had multiple seizure types (p=0.01) and prevalent involvement of temporal regions (p=0.02). A higher prevalence of episodes of SE was found in the antibody-negative group (p<0.001). Immunotherapy was prescribed in 88.60%, and effective in 61.80%. Independent predictors of favourable outcome of the AE were early immunotherapy (p<0.001) and the detection of antineuronal surface antibodies (p=0.01). Autoimmune-associated epilepsy was the long-term sequela in 43.73%, associated with cognitive and psychiatric disturbances in 81.73%. Independent predictors of developing epilepsy were difficult to treat seizures at onset (p=0.04), a high number of antiseizure medications (p<0.001), persisting interictal epileptiform discharges at follow-up (p<0.001) and poor response to immunotherapy during the acute phase (p<0.001). Conclusions: The recognition of seizures secondary to AE represents a rare chance for aetiology-driven seizures management. Early recognition and treatment at the pathogenic level may reduce the risk of long-term irreversible sequelae. However, the severity of seizures at onset is the major risk factor for the development of chronic epilepsy. This study provides class IV evidence for management recommendations.